PELATIHAN PEMBUATAN VIDEO ANIMASI MENGGUNAKAN PLATFORM ANIMAKER BAGI GURU MATEMATIKA SMP - Elfi Rahmadhani; Julia Noviani (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
Technological advances in the 5.0 era have become a core role in various fields, including in the field of education. The skills of making interesting learning material videos are urgently needed by teachers today. The purpose of this community service activity is to assist junior high school mathematics teachers in making animated videos of learning materials using the Animaker online platform. This service activity was carried out at SMPN 10 Takengon by involving junior high school mathematics teachers who are members of the Central Aceh MGMP forum. This activity was carried out on February 9, 2023. Activities in community service were carried out through three stages, namely the preparation stage, the implementation stage which consisted of workshops and practices and the evaluation stage. From the results of the activity, the MGMP Aceh Tengah math teachers gave a positive response to this activity as evidenced by the results of the evaluation using Mentimeter